Reaping or Losing Digital Dividend? The Use of Social Media for Enhancing Public Participation: A Literature Review - Wiraniskala, Bella; Sujarwoto, Sujarwoto (FIA UB, 2020)
The Internet has made social media a rapidly moving and vigorous domain and has changed the landscape for communications. It has changed different processes and engagement of human interaction and it is becoming hard to separate from people lives. The population of the internet and social media user are growing bigger every day, and so the opportunity for public participation. This study subsequently will identify of how government can take advantage of that digital dividend. To understand the issue, this research used a robust systematic literature review approach. The findings conclude that social media could help citizens to connect online and organize faster for collective action in order to put pressure when government performance does not meet people expectation.